Sirius (V-Unframed, 2021)
An Experience developed as an isolation countermeasure for the SIRIUS isolation study which aims to find ways to mitigate the psychological effects of isolation. This research project is run in collaboration between the ESA, NASA, UAE Space Agency, Germany’s DLR, and the Moscow IBMP involving experiments from teams from all around the world. A small crew will spend 8 months in isolation, simulating the experience of being on Mars. During that time they will use a VR experience developed in SFU's iSpace Lab to reflect on their connection to earth and humanity as well as the importance of their own mission as a way to feel less isolated. At V-Unframed, immersants will get the chance to try out a short (5-minute) or full (20-minute) version of the experience, beginning on earth and being taken for a stimulating yet relaxing journey into space.
Keywords: Riecke; Riecke_2021; VR exhibition; alex-kitson; ashu-adhikari; bernhard-riecke; denise-quesnel; exhibit; john-desnoyers-stewart; katerina-stepanova; noah-miller; patrick-pennefather; proj--sirius; talkWithoutPaper; thesis-related